2021
DOI: 10.1108/jarhe-03-2021-0111
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of factors influencing intercultural communication competence of the international students from a higher education institute in Malaysia

Abstract: PurposeThe purpose of this study is to highlight the importance of intercultural communication competence (ICC) of international students living in Malaysia. This study considered the culture-general factors of integrated model of ICC (IMICC) established from the West with an addition of empathy and further addressed these influencers on the international students from a Malaysian university. It is proposed that empathy, sensation seeking, ethnocentrism, attitude and motivation have a direct influence on ICC.D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Ethnocentrism is a variable that had a negative relationship with ICC as well as weakened the relationship between other variables that contribute to ICC (Arasaratnam, 2007). On the contrary, various studies found that ethnocentrism fails to impact ICC of the students (Nadeem et al, 2020b(Nadeem et al, , 2021.…”
Section: Ethnocentrismmentioning
confidence: 99%
See 4 more Smart Citations
“…Ethnocentrism is a variable that had a negative relationship with ICC as well as weakened the relationship between other variables that contribute to ICC (Arasaratnam, 2007). On the contrary, various studies found that ethnocentrism fails to impact ICC of the students (Nadeem et al, 2020b(Nadeem et al, , 2021.…”
Section: Ethnocentrismmentioning
confidence: 99%
“…The findings indicated that sensation seeking positively affects the communication with people of different cultural backgrounds. Recently, Nadeem et al (2021) witnessed that sensation seeking is one of the significant indicators of ICC.…”
Section: Sensation Seekingmentioning
confidence: 99%
See 3 more Smart Citations